Positive maternal attitudes to following healthy infant feeding guidelines attenuate the associations between infant appetitive traits and both infant milk intake and weight. (1st June 2021) - Clifton, Emma A.D.; Ahern, Amy L.; Day, Felix R.; Sharp, Stephen J.; Griffin, Simon J.; Ong, Ken K.; Rajalakshmi Lakshman,
Abstract: Appetitive traits influence food intake and weight gain throughout the life-course. Here, we investigated whether maternal attitudes to following healthy infant feeding guidelines could modify this association. Baseline data from 544 mother-infant formula-feeding dyads recruited to the Baby Milk Trial were included in this observational, cross-sectional analysis. Infant appetitive traits (food responsiveness and satiety responsiveness), maternal attitudes to following healthy infant feeding guidelines (self-efficacy, outcome-expectancy, intentions) and infant milk intakes were reported by mothers through questionnaires. Infant weight was measured using standard procedures. Associations between the maternal attitudes score or infant appetitive traits with infant milk intake and infant weight were evaluated in linear regression models adjusted for infant sex and age. To identify effect modification, the interaction term between the maternal attitudes score and infant appetitive trait was added to the model. Infants' mean age and weight were 2.3 months (SD = 0.9) and 5.5 kg (SD = 0.9), respectively. The mean daily infant milk intake reported by mothers was 895 ml/day (SD = 215). Higher maternal attitudes score was associated with lower infant milk intake (Beta = −68.4 ml/day/unit (95% CI: 96.6, −40.2)) and infant weight (Beta = −0.13 SD/unit (−0.25, −0.02)). The maternal attitudes score showed interactions with infant food responsiveness on infant milk intake ( p  = 0.049), and with infant satiety responsiveness on infant weight ( p  = 0.01). In both cases, a higher maternal attitudes score attenuated the associations between infant appetitive traits and those outcomes. This analysis provides evidence that positive maternal attitudes to following healthy infant feeding guidelines attenuate the effects of infant appetitive traits on infant milk intake and body weight. Highlights: No previous studies have examined the role of maternal attitudes on infant weight. Positive maternal attitudes attenuate the influence of infant appetitive traits on weight. Maternal attitudes are a possible target for interventions to promote healthy growth.